The Air Apparent - Rao, Joe (Natural history, 2020)
Visibility will be confined to central and east Africa, eastern Europe, western and central Asia, most of Indonesia, and Australia. 6 Venus rises just fifteen minutes before the Sun, as seen from latitude 40° north, and probably only visible with binoculars. 8 Jupiter and Saturn team up with the waning gibbous Moon late this evening. During June as its distance from Earth decreases from 94 million to 76 million miles, the planet correspondingly brightens from 0 to -0.5 magnitude. 19 Very low above the eastnortheast horizon about fortyfive minutes before sunrise, look for Venus (magnitude -4.4) and the narrow sliver of a waning crescent Moon. At 4:47 UTC, a full annular solar eclipse appears in central Africa and follows a path across Africa, the Arabian Peninsula, the Indian subcontinent, China, the Philippine Sea, and, finally, the North Pacific Ocean at 8:32 UTC.